2020
DOI: 10.1186/s43019-020-00067-y
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of functional outcomes between single-radius and multi-radius femoral components in primary total knee arthroplasty: a meta-analysis of randomized controlled trials

Abstract: Purpose Our purpose in the current meta-analysis was to compare the functional outcomes in patients who have received single-radius (SR) or multi-radius (MR) femoral components in randomized controlled trials (RCTs) for primary total knee arthroplasty (TKA). The hypothesis was that there would be no statistically significant difference between two groups in terms of functional outcomes. Materials and methods We searched the internati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 52 publications
1
10
0
Order By: Relevance
“…It attempts, at least in theory, to provide more lever arm for the extensor mechanism and thus improve strength. Current evidence did not show any significant differences between these two femoral component designs regarding functional outcomes [18].…”
Section: Knee Replacementmentioning
confidence: 62%
“…It attempts, at least in theory, to provide more lever arm for the extensor mechanism and thus improve strength. Current evidence did not show any significant differences between these two femoral component designs regarding functional outcomes [18].…”
Section: Knee Replacementmentioning
confidence: 62%
“…In a meta-analysis investigating the functional outcomes in patients who have received SR or MR femoral components in randomized controlled trials for primary MA-TKA, no significant differences were found between the two groups. 32 In the future, a detailed comparison between MA and KA-TKA with SR or MR prosthesis should be performed.…”
Section: Discussionmentioning
confidence: 99%
“…The effect of the single-radius implant has been well studied with 2D analysis. 24 This implant type is defined as a single spherical radius with a locus between 10 and 120 . 24 There is evidence to suggest that this implant design may be associated with a statistically significant improvement in motion analysis parameters.…”
Section: Studying Implant Choicementioning
confidence: 99%
“…24 This implant type is defined as a single spherical radius with a locus between 10 and 120 . 24 There is evidence to suggest that this implant design may be associated with a statistically significant improvement in motion analysis parameters. Specifically, decreased flexion peak torque, increased extension peak torque, and lower flexor/extensor ratio were seen in combination with increased KSS scores from 80.3 ± 1.90 to 86.6 ± 1.89 with this implant type.…”
Section: Studying Implant Choicementioning
confidence: 99%